A comparative study of skin transcriptomes and histological observations for black and white hair colors of giant panda - Wang, Yingyun; Liang, Shangyue; Tu, Shaotong; Shen, Zhangqi; Dong, Yanjun; Liu, Gang; Shi, Hao; Jin, Yipeng (Frontiers in Medicine, 2022)
The Giant pandas (Ailuropoda melanoleuca) are mammals belonging to the bear family, order Carnivora, and their characteristic hair color and distribution has been in the spotlight. In recent years, the gradual prevalence of skin diseases in giant pandas and even the discovery of albino individuals have made the study of the substrate of their skin hair distribution more and more urgent. In this study, by comparing the skin histology and transcriptome sequencing under different color hairs of giant pandas, we found that the melanin content of hair follicles at the base of black and white hairs differed, but the hair follicles at the base of white hairs also contained some amount of melanin. The transcriptome sequencing results showed that there were great differences in the expression of the transcriptome of the same flesh-pink skin under different hair color blocks, in which the number of differentially expressed genes in the white skin was much smaller than that in the black skin. And there were four groups of genes with different expression levels between black and white hair color. The skin with different hair color had different KEGG pathway enrichment in tumor, cell adhesion and melanin development related signal pathways.